PENERAPAN METODE WEIGHTED PRODUCT (WP) UNTUK PENERIMAAN PEGAWAI BARU DI PT. TIGA SERANGKAI PUSTAKA MANDIRI SURAKARTA - Nur Rohmah, Dwi Remawati, Andriani KKW (STMIK Sinar Nusantara, 2016)
PT. Tiga Serangkai Pustaka Mandiri Surakarta is a company engaged in printing, publishing, book stores, and distributors. In the process of recruiting new employees, every year the number of applicants has increased while the number of employees who received restricted so necessary to make a decision-making system that can facilitate HR managers in selecting candidates for new employees in accordance with the needs and the company's criteria. The purpose of this research is to build a system by applying the method of Weighted Product (WP). This method is one method of settling the multi-criteria in recruitment where many of the criteria that should be considered by finding the weight values for each criterion, then do ratings process that will determine the best alternative to prospective employees. The weight of the criteria in the selection of candidates for the new employee at the selection stage of administration is the last education (15%), the suitability of the majors (20%), GPA (15%), age (10%), work experience (15%), the suitability of work experience ( 25%). The analysis of new personnel recruitment system shows that the selection and administration have accuracy levels of 80% and a selection test has a level of accuracy of 66.67%. Keywords: Weighted Product, Recruitment, Selection